The importance of anti-Serb propaganda and hybrid warfare in the process of the disintegration of Yugoslavia - Jevtović, Zoran B. (Napredak, 2021)
The paper focuses on a synthesized image of the propaganda, engineered and coordinated by the totalitarian media of leading Western countries during the 1990s, which reduced the complex Yugoslav reality to spin-off propaganda images that laid the blame on only one side. The negative perception of Serbs was achieved by framing propaganda narratives, created by a strong campaign of well-organized and influential global media. By powerful stigmatization and demonization in political practice, Serbs were branded as responsible for all the conflicts and wars. Combining different methods and techniques of psychological, propaganda and armed activities at the operational or tactical level, Western strategists dedicated a significant part of their engagement to stifling alternative sources of information. This included even their physical destruction, which was realized for the first time in world practice with the NATO bombing of the building of the Serbian Radio and Television and over 300 relays and repeaters. Yugoslavia was gradually torn apart, in line with the interests of the new geopolitical environment, while the Serbs did not quickly understand the process in which, instead of the truth, manipulative notions of „new reality” spread through the global media.